The Spatial Distribution of Bed Sediments at Krueng Cut Estuary: The Sieve Analysis Approach - Irham, Muhammad; Fibriarista, Ika; Sugianto, Sugianto; Setiawan, Ichsan (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2017)
This research studied the characteristic of bed sediment in the estuary of Krueng Cut, Banda Aceh. Analyzing the field samples from different site of stations along the channel from upstream to estuary shows different pattern and profile of deposited bed sediment. Therefore, sorting the size of sediment is important spatially because pattern of its deposition and characteristic will illustrate how distribution patterns indicate the nature of the channel. Hence, the study aims to determain the pattern of bed sediment distribution as well as its profile spatially. To implement the intended purpose, the coring method was employed by using purposive random sampling for 15 stations of taken sampling. The sample of sediment was proceeded by using a 2,5 cm diameter of PVC paralon at the depth of 25 cm from the bathymetry base. Sample was analyzed using wet sieve analysis method. The result informed that the dominant of bed sediment size are medium sand found around the mouth of the river, fine sand existed along the mixing area, and very fine sand occurred in the transition zone. Inthe region of coastal dynamic, the sediment was dominated by medium sand size, meanwhile in the area of river dominated flow, the sediment is subject to fine sand size.Thus, the fraction of very fine sand size of sediment was found in the zona of transition.